2015
DOI: 10.1038/nrurol.2015.252
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding and treating premature ejaculation

Abstract: Over the past several years, many advances have been made in our understanding of the epidemiology, pathophysiology, and management of premature ejaculation. Newly developed definitions of premature ejaculation are now available, and our perception of the classification, prevalence, aetiological factors, and treatment options for premature ejaculation have evolved. Despite ongoing research, there remains much to be learned about all aspects of this common sexual disorder, in particular effective clinical diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 187 publications
1
29
0
2
Order By: Relevance
“…Although PE was initially described more than a century ago, 14 its definition, epidemiology, and management continue to be a matter of discussion among physicians 15 . Our findings confirmed that there are many differences among sexual health experts in their understanding of PE.…”
Section: Discussionsupporting
confidence: 76%
“…Although PE was initially described more than a century ago, 14 its definition, epidemiology, and management continue to be a matter of discussion among physicians 15 . Our findings confirmed that there are many differences among sexual health experts in their understanding of PE.…”
Section: Discussionsupporting
confidence: 76%
“…Vast advances have occurred over the past decade with regards to understanding the epidemiology, pathophysiology and management of premature ejaculation (PE) (1); however, we still have much to learn about this common sexual problem. As a standardized evidence-based definition of PE has only recently been established (2), the reported prevalence rates of PE prior to this definition have been difficult to interoperate.…”
Section: Introductionmentioning
confidence: 99%
“…Having previously been considered singly as a psychologically disorder, PE is now understood to be far more complex with multiple etiological factors playing a role in its pathogenesis (5). These advances in understanding PE necessitated the development of an evidence-based definition and classification to enable the scientific community to design methodologically rigorous studies on the topic.…”
Section: Introductionmentioning
confidence: 99%